Discriminant analysis in the classification of the preparation strength girls 11-12 year - Ivashchenko, Olga; Cieślicka, Mirosława (Journal of Education, Health and Sport, 2016)
Material and methods: To achieve the goal, the following research methods: analysis of scientific literature, analysis of test results developed selected statistical methods. The study involved 21 girls 11 years old and 26 girls 12 years old. Results: The analysis shows that the most statistically significant differences in the test results of girls 6 and 7 classes have been observed in studies 2 "standing long jump (p <0.001). Conclusions: Structural factors canonical discriminant function suggests that more attention is paid to training, speed endurance, the greater the likelihood of increased motor preparation of girls 11-12 years old. The canonical discriminant function can be used to assess and forecast the development of motor skills in girls 11-12 years old.